2019
DOI: 10.1021/acssynbio.9b00379
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Cytochrome c Maturation Can Increase the Bioelectronic Performance of Engineered Escherichia coli

Abstract: Genetic circuits that encode extracellular electron transfer (EET) pathways allow the intracellular state of Escherichia coli to be electronically monitored and controlled. However, relatively low electron flux flows through these pathways, limiting the degree of control by these circuits. Since the EET pathway is composed of multiple multiheme cytochromes c (cyts c) from Shewanella oneidensis MR-1, we hypothesized that lower expression levels of cyt c may explain this low EET flux and may be caused by the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 60 publications
5
42
0
Order By: Relevance
“…To prepare E. coli for cathodic conditions, individual strains were first grown aerobically, incubated in potentiostatic-controlled bioreactors under anaerobic, anodic conditions (ΔV=+200 mV Ag/AgCl ) for at least one day. Under these conditions, the CymAMtr -E. coli strain produced a significant steady-state current, while Ccm -E. coli and Mtr -E. coli produced much lower currents ( Figure 2A ), reinforcing that CymA is important for current production 16–18 . As anaerobic conditions were maintained, the electrode bias was then switched to cathodic conditions (ΔV= −560 V Ag/AgCl ), fumarate was added, and current consumption was measured.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…To prepare E. coli for cathodic conditions, individual strains were first grown aerobically, incubated in potentiostatic-controlled bioreactors under anaerobic, anodic conditions (ΔV=+200 mV Ag/AgCl ) for at least one day. Under these conditions, the CymAMtr -E. coli strain produced a significant steady-state current, while Ccm -E. coli and Mtr -E. coli produced much lower currents ( Figure 2A ), reinforcing that CymA is important for current production 16–18 . As anaerobic conditions were maintained, the electrode bias was then switched to cathodic conditions (ΔV= −560 V Ag/AgCl ), fumarate was added, and current consumption was measured.…”
Section: Resultsmentioning
confidence: 75%
“…To couple an electrode to specific redox molecules in a bacteria of our choosing, we and others have introduced genes from the Mtr pathway from Shewanella oneidensis MR-1 into heterologous bacterial hosts 1418 . Under anaerobic conditions, S. oneidensis can use the Mtr pathway to transfer electrons from catabolism to produce a current at an extracellular electrode ( Figure 1A ).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Expressing these cyt c requires the cytochrome c maturation (Ccm) system, which covalently ligates heme groups to the apo-protein (Sanders et al, 2010; Verissimo et al, 2011). We and others have found that expressing components of the Mtr pathway and the Ccm system enables E. coli to perform EET (Jensen et al, 2016; Su et al, 2020; TerAvest et al, 2014). In the Ccm systems of Gram-negative bacteria, CcmH is essential to the heme ligation process (Sanders et al, 2010), which includes translocating heme groups, and formatting a thioether bond between the heme group and the apo cyt c. We recently found that mutations in the C-terminal domain of CcmH can significantly change the EET efficiency by changing the stoichiometry of the Mtr cyt c (Su et al, 2020).…”
Section: Introductionmentioning
confidence: 95%
“…We and others have found that expressing components of the Mtr pathway and the Ccm system enables E. coli to perform EET (Jensen et al, 2016; Su et al, 2020; TerAvest et al, 2014). In the Ccm systems of Gram-negative bacteria, CcmH is essential to the heme ligation process (Sanders et al, 2010), which includes translocating heme groups, and formatting a thioether bond between the heme group and the apo cyt c. We recently found that mutations in the C-terminal domain of CcmH can significantly change the EET efficiency by changing the stoichiometry of the Mtr cyt c (Su et al, 2020). This finding suggested that optimizing the heme ligation process by redesigning CcmH could remodel the stoichiometry of cyt c and enhance the bioelectrical performance of Mtr-expressing E. coli.…”
Section: Introductionmentioning
confidence: 95%